Oral health perceptions, knowledge and practices among Primary Schoolchildren - Isabel Cristina Gonçalves Leite; Taís Rocha Figueira (Faculdade São Leopoldo Mandic, 2008)
Objectives: To evaluate the socioeconomic conditions, perceptions, knowledge and practices with regard to oral health in a sample ofschoolchildren from the "Escola Estadual Vieira Marques", located in the municipality of Santos Dumont - Minas Gerais, Brazil, as a mechanism for obtaining funding to develop educational actions in health suited to this population's reality. Methods: The sample consisted of 100 primary schoolchildren in the 3rd and 4th grades, participants in the Municipal program of attention to oral health developed at the above-mentioned school. The instrument used for field research was an illustrated questionnaire composed of six multiple choice questions. Results: The results indicated that there is greater emphasis on oral health, but as a means of caries prevention, demonstrating incomplete knowledge about the role of diet.Conclusion: It was concluded that it is necessary to reformulate the Municipal program of attention to oral health ("Programa Municipalde Atenção a Saúde Bucal"), in order to extend the scope of contents it touches on to beyond tooth brushing techniques; to establishpartnerships with the school staff, schoolchildren's parent and the community; and it is also necessary to use the largest possible numberof activities and motivating illustrations that cause greater impact on the children.